2016
DOI: 10.4103/0972-124x.194270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of subgingivally delivered simvastatin gel in chronic periodontitis patients

Abstract: Background:Simvastatin (SMV), a new locally delivered drug of class statins, is a specific competitive inhibitor of 3-hydroxy-2-methyl-glutaryl coenzyme A reductase. Statins, besides having lipid-lowering abilities, also have pleiotropic effects like host modulation and bone regeneration. The present study was designed to investigate the effectiveness of SMV, 1.2 mg, in an indigenously prepared biodegradable controlled-release gel as an adjunct to scaling and root planing (SRP).Materials and Methods:A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
3
8
0
5
Order By: Relevance
“…Notably, 17 out of 32 clinical studies were carried out by the same group of researchers on similar population; therefore, generalizations should be drawn with caution. Additionally, in most studies involving statins, the follow-up period was no longer than 9 months [ 103 , 130 ]. Hence, it is imperative to follow clinical studies for periods longer than those commonly investigated so as to achieve a deeper and more genuine insight into their long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 17 out of 32 clinical studies were carried out by the same group of researchers on similar population; therefore, generalizations should be drawn with caution. Additionally, in most studies involving statins, the follow-up period was no longer than 9 months [ 103 , 130 ]. Hence, it is imperative to follow clinical studies for periods longer than those commonly investigated so as to achieve a deeper and more genuine insight into their long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…19 The local delivery of simvastatin in grade II furcation defects and in periodontal pockets enhances the outcome of mechanical therapy resulting in reduced pocket depths, improved attached gain and bone fill. 20,21 Alkaline phosphatase has been measured in GCF to examine the relationship between periodontal conditions and disease activity. Increased alkaline phosphatase activity in relation to inflammation is observed in gingivitis and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Subgingivally delivered simvastatin gel in chronic periodontitis could enhance the beneficial effect of scaling and root planing (SRP) in pocket reduction, gain in CAL, and bone loss. [72] The effect of different concentrations of local Rosuvastatin (0.1 and 1 mg) in calvarial bone defects was studied, and it was observed that local administration of 1 mg of Rosuvastatin enhanced bone regeneration in calvarial rat defect. [73] Systematic review and meta-analysis find that adjunctive use of locally delivered statins to mechanical SRP is beneficial to increasing bone fill percentage.…”
Section: Evidence Based Overview Linking Periodontal Infection and Hymentioning
confidence: 99%